The role of TRPM2 channels in neurons, glial cells and the blood-brain barrier in cerebral ischemia and hypoxia - TURLOVA Ekaterina; FENG Zhong-ping; SUN Hong-shuo (Acta Pharmacologica Sinica, 2018)
Abstract Stroke is one of the major causes of mortality and morbidity worldwide, yet novel therapeutic treatments for this condition are lacking. This review focuses on the roles of the transient receptor potential melastatin 2 (TRPM2) ion channels in cellular damage following hypoxia-ischemia and their potential as a future therapeutic target for stroke. Here, we highlight the complex molecular signaling that takes place in neurons, glial cells and the blood-brain barrier following ischemic insult. We also describe the evidence of TRPM2 involvement in these processes, as shown from numerous in vitro and in vivo studies that utilize genetic and pharmacological approaches. This evidence implicates TRPM2 in a broad range of pathways that take place every stage of cerebral ischemic injury, thus making TRPM2 a promising target for drug development for stroke and other neurodegenerative conditions of the central nervous system.